KONTRIBUSI DAN STRATEGI SEKTOR PERIKANAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN TIMOR TENGAH SELATAN - Kabul Putra Imanuel Mone; Donny T. S. Junias; Thobias E. D. Tomasowa (P3M- Politeknik Negeri Kupang, 2020)
This research aims to determine how much the contribution of the fisheries sector to local own-source revenue and also to find out how to increase local revenue from the fisheries sector. The data collection techniques used in this study were interviews and documentation. The data analysis technique used is the contribution analysis and SWOT analysis. Contribution analysis used to find out how much the fisheries sector's contribution to Regional Original Income, SWOT analysis is used to find out how to increase local own-source revenue from the fisheries sector. Based on the data analysis conducted, it is concluded that: The contribution of the fisheries sector to local own-source revenue in 2015 was 0.0011%; in 2016 it increased to 0.0029% than in 2017 increased to 0.0032%. However, in 2018 it decreased to 0.0027%, but in 2019 it increased again to 0.0040%. Then from the SWOT analysis, the Regional Government of South Central Timor Regency can increase local own-source revenue from the fisheries sector by optimizing the available funds to cultivate a supportive geographic and training Human Resources to take advantage of market availability.